2022
DOI: 10.3390/en15072642
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Learn about Drivers for Industrial Energy Efficiency—Current State of Knowledge

Abstract: Drivers for industrial energy efficiency are factors that promote the sustained adoption of energy-efficient measures and practices. Leveraging drivers to overcome barriers and encourage action which improves industrial energy efficiency can contribute to closing the energy efficiency gap. In fossil-fuel-based systems, this will also contribute to greenhouse gas abatement. A systematic literature review was used to investigate how knowledge about drivers is generated and whether prevalent drivers can be mapped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The systematic literature review conducted by [61] confirmed that surveys and/or interviews with managers are the most commonly employed method for gathering data on drivers for industrial energy efficiency. Similarly, our research is based on data obtained from the European Manufacturing Survey (EMSurvey), specifically the sub-samples for Austria [62], Lithuania [63], Slovakia [64], and Croatia and Slovenia [65], which covers mostly the central European region.…”
Section: Datamentioning
confidence: 88%
“…The systematic literature review conducted by [61] confirmed that surveys and/or interviews with managers are the most commonly employed method for gathering data on drivers for industrial energy efficiency. Similarly, our research is based on data obtained from the European Manufacturing Survey (EMSurvey), specifically the sub-samples for Austria [62], Lithuania [63], Slovakia [64], and Croatia and Slovenia [65], which covers mostly the central European region.…”
Section: Datamentioning
confidence: 88%
“…Unfortunately, a significant portion of Indian research is absent. Most of the published research is focused on energy efficiency because energy is a key global problem and the country is rapidly expanding in terms of population, consumption of goods and energy consumption (Ahmad et al, 2020;Sindhwani et al, 2018;Smith et al, 2022). There is a gap in reported literature from the angle of drivers and barriers of climate change mitigation from IISI.…”
Section: Modeling Drivers and Barriers Of Ccmsmentioning
confidence: 99%